The effect of comparative competition style on the performance of the skills of handling and handball for students aged (13-14) years in Baghdad governorate - Jaber, Suaad Sadi; Jaber, Suaad Sadi (International Journal of Psychosocial Rehabilitation, 2020)
Given that the school is the educational body that deals with the fields of education for male and female students in the community, the physical education lesson has become the circle that complements the school curriculum, which provides students with experiences to practice sports activities and that works to improve their motor performance in addition to their basic skills in handball during the exercises that take place and since the game of handball is an enjoyable team game for both practitioners and spectators, it is used widely and widely because it contains many skills, including handling and wetting skills, which are important skills in handball, and the importance of research is that it is an attempt by Researcher to present the method of comparative competition in teaching handling skills and handball to female students of (13-14) years, respectively. To reach the final results that serve physical education teachers in the field of teaching handling and handball skills in the SP school. The research objectives are: 1. Development of the vocabulary of an educational program using the comparative competition method to teach handling and handball skills for students between (13-14) years old in Baghdad governorate. 2. Identify the effect of the comparative competition method on teaching handball skills to female students (13-14) years old in Baghdad governorate. 3. Identify the effect of the comparative competition method in teaching the skill of female students with handball to students (13-14) years old in Baghdad governorate.